La Internet Y Su Incidencia En El Rendimiento Académico De Los Y Las Estudiantes De Los Décimos C Y E Del Colegio Nacional Adolfo Valarezo De La Ciudad De Loja Periodo 2013 -2014 - Tillaguango, Mónica Irene (2016)
This research, "the internet and its impact on the academic performance of the students of the tenth "C and E" of the College National Adolfo Valarezo city Loja period 2013 - 2014", took the general objective, guide to the proper use of the internet as means of research, information and commu-nication, implementing intervention strategies which allow the student to develop scientific knowledge technological, so thus they have good intel-lectual and academic development, it is an information and awareness action. The specific objectives, allowed establishing actions or activities of theo-retical and methodological basis is what made it easier to learn the con-cepts related to the theme of the internet and its impact on the academic performance of students, determining the main causes of the inappropriate use of the internet. In regards to methodology, research is part of a study scientific, historical, inductive, deductive, descriptive, analytical, synthetic and statistical characteristics, to explain and provide alternative solutions to the problem of research ¿the internet and its incidence in the academic performance of the students of the tenth C and E of the Colegio Nacional Adolfo Valarezo from the city of Loja period 2013-2014? In the development of this investigative work is compiled the necessary information through the application of instruments of research such as: the surveys, and observation sheet the same applied to the students of the tenth C and E and plant teacher of the College National Adolfo Valarezo, in order to obtain accuracy and reliability of the research, demonstrate clearly that the students the make a bad use of the internet, which hinders their learning, and thus affects their academic performance. Faced with this reality, silvers a proposal for transforming, and pedagogi-cal intervention that will allow the Department of guidance and counseling students, educate and raise awareness among students and parents of the serious consequences caused by the misuse of the internet in the lives of youth; so this focus the proper use of the internet, to its intellectual and academic performance.